Immunogenicity of different dosing schedules of the human live attenuate rotavirus vaccine (RV1) in infants and children: a meta-analysis. Issue 6 (3rd June 2019) - Dai, Xiting; Bai, Ruolan; Jian, Miaomiao; Ji, Zhenhua; Ding, Zhe; Wang, Feng; Bi, Yunfeng; Manzamaesso, Abi; Chen, Taigui; Luo, Lisha; Liu, Aihua; Bao, Fukai
ABSTRACT: Rotavirus immunization strategies have become part of a comprehensive global public health program to control rotavirus-associated gastroenteritis, particularly in infants and children in developing countries. Several studies have reported the efficacy of different rotavirus vaccine dosing schedules, but with mixed findings. Therefore a systematic review of the published literature on rotavirus vaccination dosing schedules using the live attenuated RV1 rotavirus vaccine in infants and children, including randomized controlled clinical trials (RCTs), published between January 1998 to January 2018 was conducted, with meta-analysis of the published data. The literature search was performed using six databases. The initial review identified 495 publications, of which three satisfied the selection eligibility criteria. The three studies that assessed RV1 rotavirus vaccine immunogenicity compared a two-dose vaccination schedule with a three-dose vaccination schedule. The use of a three-dose vaccination schedule did not show a statistically significant seroconversion rate when compared with a two-dose vaccination schedule (OR = 0.87; 95% CI, : 0.65–-1.17;, p- = 0.298). Analysis of included studies with one-month follow-up time showed that the three-dose vaccination schedule did not result in have significantly increased geometric mean concentrations (GMCs) compared with the two-dose vaccination schedule (p = 0.311).Rotavirus immunogenicity did not increase significantly with the three-dose schedule at 6, 10 and 14 weeks with the two-dose schedule at 10 and 14 weeks. These findings indicate that further controlled studies should be undertaken to support the optimum immunization schedules for rotavirus in terms of clinical effectiveness and cost-effectiveness, particularly for infants and children in developing countries.